Moral Judgement in Early Bilinguals: Language Dominance Influences Responses to Moral Dilemmas - Wong, Galston; Ng, Bee Chin (Frontiers in Psychology, 2018)
The Foreign-Language effect (FLe) on morality describes how late bilinguals make different decisions on moral judgements, when presented in either their native or foreign language. However the relevance of this phenomenon to early bilinguals, where a language’s ‘nativeness’ is less distinct, is unknown. This study aims to verify the effect of early bilinguals’ languages on their moral decisions and examine how language experience may influence these decisions. Eighty-six early English-Chinese bilinguals were asked to perform a moral dilemmas task consisting of personal and impersonal dilemmas, in either English or Mandarin Chinese. Information on language experience factors were also collected from the participants. Findings suggest that early bilinguals do show evidence of a language effect on their moral decisions, which is dependent on how dominant they are in the language. Particularly, the more dominant participants were in their tested language, the larger the difference between their personal and impersonal dilemma response choice. In light of these findings, the study discusses the need to re-examine how we conceptualise the FLe phenomenon and its implications on bilinguals’ moral judgement. It also addresses the importance of treating bilingualism as multidimensional, rather than a unitary variable.